EFFECT OF CAPITAL DEQUACY RATIO AND NON PERFORMING FINANCING ON RETURN ON ASSET IN PT. BANK RAKYAT INDONESIA (BRI) SYARIAH PERIOD 2012-2016 - Jatmiko, Udik; Srikalimah, Srikalimah; Fitriyanto, Doni (Universitas Pendidikan Ganesha, 2017)
The purpose of this study to analyze and determine the effect between Capital Adequacy Ratio and Non Performing Financing on Return On Asset At PT. Bank Rakyat Indonesia (BRI) Syariah Period 2012-2016. The research framework is taken from the financial statements at PT. Bank Rakyat Indonesia (Persero) Tbk. Taken from the Indonesia Stock Exchange for the last 5 (five) periods of 2012, 2013, 2014, 2015 and 2016. The research approach used is a quantitative approach, the method of analyzing data, among others: (1) Multiple Linear Regression Analysis, 2) F Test Analysis, (3) Test T. (4) Determinant Coefficient Test. The results obtained that Capital Adequacy Ratio (CAR) partially significant positive effect on Return On Assets (ROA) in PT. Bank Rakyat Indonesia Syariah Period 2012-2016. Non Performing Financing (NPF) ratio has no effect on Return On Asset (ROA) in PT. Bank Rakyat Indonesia Syariah Period 2012-2016.Capital Adequacy Ratio and Non Performing Financing simultaneously have a really significant effect on Return On Assets at PT. Bank Rakyat Indonesia Syariah.